Minority within: 2nd generation young adult muslim Australian in ten things i hate about me - Raihanah, M.M.; Norzalimah Mohd. Kassim,; Ruzy Suliza Hashim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
It is undeniable that in the era of globalisation, the young adults’ world is becoming ever fluid and expandable. For the young adult of minority descent, the challenges are made more complex given the contestation with the majority culture of the land. This paper investigates the contestation of marginalization by a Muslim young adult in multi-ethnic, multi-cultural Australia as portrayed in Randa Abdel-Fattah’s second novel entitled Ten Things I Hate About Me. The paper discusses two fundamental identity spaces within the discourse of multiculturalism – private and public, and examines how the social, cultural and religious spaces inhabited by the young adult minority protagonist influence her in the formation of her identity as a member of a minority community in a predominantly white majority society. Pitted as the ‘minority within’ for the marginalization that the protagonist feels within her immediate family circle, the experience of the young adult minority, as this paper suggests, is ever complex.